Light-Induced Higher-Order Bragg Resonance in Heliconical Cholesteric Liquid Crystals - Ashot H. Gevorgyan; Francesco Simoni (Crystals)
Higher-order reflections from a cholesteric liquid crystal have been investigated for a long time after early observations of an oblique incidence of light. Even with the restriction of the required oblique geometry, wavelength tuning would make this property very attractive for photonic applications in the near-UV range of the electromagnetic spectrum. Unfortunately, this is quite difficult to achieve in cholesterics, and it has been obtained in special configurations that lead to the deformation of the helical structure. We show here that a new opportunity is provided by heliconical cholesteric liquid crystals and demonstrate that second-order Bragg resonance with high reflectivity and a narrow band can be produced by a light beam with intensity high enough to give rise to a significant optical torque with the consequent distortion of the helical structure. Exploiting the well-known properties of heliconical cholesterics under electric fields, we also demonstrate that the easy tuning of the second-order reflection band is achieved in the near-UV range.